Application of decoy oligodeoxynucleotides strategy for inhibition of cell growth and reduction of metastatic properties in nonresistant and erlotinib‐resistant SW480 cell line. (13th January 2021) - Asadi, Zoleykha; Fathi, Mojtaba; Rismani, Elham; Bigdelou, Zahra; Johari, Behrooz
Abstract: Signal transducer and activator of transcription 3 (STAT3) is a critical regulator for angiogenesis, cell cycle progression, apoptosis, and drug resistance. Resistance toward EGF receptor (EGFR) inhibitors is a significant clinical concern for metastatic colon cancer patients. The present study aimed to evaluate the blocking influences of STAT3 decoy oligodeoxynucleotides (ODNs) on the STAT3 survival signaling pathway in nonresistant and erlotinib‐resistant SW480 colon cancer cells. First, STAT3 decoy and scramble ODNs were designed according to STAT3 elements in the promoter region of MYCT1 gene and tested for the interaction of STAT3 protein with designed ODNs via in silico molecular docking study. Then, the efficiency of transfection and subcellular localization of ODNs were assessed using flow cytometry and fluorescence microscopy, respectively. Cell viability, cell cycle, and apoptosis tests, scratch and colony formation assays, and real‐time PCR were also used to study the cancerous properties of cells. A considerable decrease in proliferation of colon cancer cells was observed with blockade of STAT3 signaling due to cell cycle arrest and induced apoptosis via downregulation of cyclin D1 and Bcl‐XL, respectively. Furthermore, upon transfecting STAT3 decoy ODNs, colony formation potential and migration activity in both SW480 colon cancer cell lines were decreased compared to the control groups. From this study, it could be concluded that STAT3 is critical for cell growth inhibition and metastatic properties reduction of resistant SW480 colon cancer cells; therefore, STAT3 decoy ODNs could be considered as potential therapeutics along with current remedies for treating drug‐resistant colon cancer. Abstract : Overview of suppressing the metastatic properties in both nonresistant and erlotinib‐resistant colon cancer cells using a signal transducer and activator of transcription 3 (STAT3) decoy oligodeoxynucleotides (ODN).